Penerapan Sampah Buah Tropis untuk Microbial Fuel Cell - Melda Latif; Arif Dwi Fajri; Mumuh Muharam (Universitas Syiah Kuala, 2020)
Microbial Fuel Cell (MFC) is one tool that uses microbes to produce electrical energy. The main components of MFC support are anodes, cathodes, and salt bridges. In this paper, the application of tropical fruit waste to MFC is presented. Tropical fruit waste used here are pineapples, oranges, bananas, watermelons, mangos, and papayas. The fruit waste is extracted and fermented to produce microbial. The microbial produces ions attached to the anode. Measurement of system current and voltage is carried out using a digital multimeter. In pineapple substrate MFC, Voc has a maximum of 485 mV, maximum current density is 163 mA/m2 and maximum power density of 11mW/m2. The orange substrate obtained Voc maximum of 805 mV, maximum current density of 661 mA/m2 and maximumpower density of 62 mW/m2. Voc banana substrate has a maximum of 312 mV, maximum current density of 118 mA/m2 and maximum power density of 5.9 mW/m2. The Voc watermelon substrate has a maximum of 451 mV, maximum current density of 306 mA/m2 and maximum power density of 18.6 mW/m2. Voc mango substrate has a maximum of 586 mV, maximum current density of 229 mA/m2 and maximum power density of 4.3 mW/m2. Voc papaya substrate is a maximum of 338 mV, maximum current density of 58 mA/m2 and maximum power density of 2.9 mW/m2. These results show the potential for renewable electricity sources.